1972
DOI: 10.1037/h0033737
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy-associated deficit in schizophrenic reaction time performance.

Abstract: Hospitalized schizophrenic patients, process and reactive as defined by the Elgin Prognostic Rating Scale, were compared with nonschizophrenic psychiatric patient controls and normal controls to assess the effects of redundancy of information on reaction lime performance. The influence of information redundancy was assessed by manipulating the degree of regularity in the presentation of preparatory interval (PI) durations. Runs of two and four identical Pis, defined as low and high redundant sets, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 20 publications
6
58
1
Order By: Relevance
“…Concerning the crossover effect, results from various studies have shown that in 47-72% of all process schizophrenics, a typical crossover pattern is manifested (referring now to the Steffy paradigm in which each series of regular preparatory interval trials is embedded in a longer irregular series (78,79)). The crossover pattern has, however, also shown to be highly prevalent in temporal lobe lesion patients, and in some groups of aged patients (48).…”
Section: Results Of Rt Studiesmentioning
confidence: 99%
“…Concerning the crossover effect, results from various studies have shown that in 47-72% of all process schizophrenics, a typical crossover pattern is manifested (referring now to the Steffy paradigm in which each series of regular preparatory interval trials is embedded in a longer irregular series (78,79)). The crossover pattern has, however, also shown to be highly prevalent in temporal lobe lesion patients, and in some groups of aged patients (48).…”
Section: Results Of Rt Studiesmentioning
confidence: 99%
“…Almost all of the available literature suggests that a high rate of process schizophrenic patients shows the RT-crossover. 6,10,11,14,17 These findings suggest that the crossover phenomenon may be a marker for process schizophrenia.…”
Section: Rss and Rt-crossovermentioning
confidence: 77%
“…Numerous schizophrenia researchers in subsequent decades have referred to Shakow's findings as solid evidence of reaction time deficits. Moreover, many have relied on this paradigm to study the crossover effect and its implications for the cognitive underpinnings of the disorder (e.g., Bellissimo & Steffy, 1972;Nideffer et al, 1971;Knehr, 1954;Rosenbaum, Taylor, & Minasian, 1997;Tizard & Venables, 1956). And although researchers have offered alternative explanations for Shakow's findings (e.g., Steffy & Galbraith, 1974), they continue to utilize Shakow's work as a starting point.…”
Section: Citation Analysismentioning
confidence: 94%